Hexagonal microspindle of NH2-MIL-101(Fe) metal–organic frameworks with visible-light-induced photocatalytic activity for the degradation of toluene. Issue 6 (7th January 2016) - Zhang, Zhiguang; Li, Xinyong; Liu, Baojun; Zhao, Qidong; Chen, Guohua
Abstract : This work focuses on exploring metal–organic frameworks (MOFs) for degradation of gaseous pollutants. Abstract : This work focuses on exploring metal–organic frameworks (MOFs) for degradation of gaseous pollutants. We demonstrate that NH2 -MIL-101(Fe) hexagonal micro-spindles, as a new photocatalyst, showed an improved performance for degradation of toluene under visible light irradiation. The structural and optical properties of the as-prepared NH2 -MIL-101(Fe) hexagonal micro-spindles were characterized. Furthermore, the catalytic reaction mechanism has been investigated on the basis of in situ Fourier Transform infrared spectroscopy (FTIR) technology. Meanwhile, some intermediates (benzoic acid) and the final product (CO2 ) of the degradation of toluene were also identified.